Exploration of Singosari Museum - Cahya, Alfanova Rifky; Wicaksono, Michael Richard Putra; Budidarma, Yudistira Oscarino; Wulansari, Rani; Yahya, Saiful (LPPM STIKI Malang, 2024)
This study, conducted by the Makar Team, students of Visual Communication Design (DKV) at STIKI Malang, aimed to develop an Augmented Reality (AR) application to assist visitors in exploring the historical context of the Singosari Museum in Malang. Utilizing the design thinking methodology, the research comprised five stages: empathize, define, ideate, prototype, and test. Direct observation was conducted during the empathize stage to understand visitor needs. Problems were formulated in the define stage, followed by ideation (ideate) and prototype development (prototype). The prototype was tested (test) to gather feedback. The results showed that the AR application significantly enhanced historical understanding and provided innovative interaction with historical information.